Influence of examiners’ experience and region of interest location on semiquantitative elastography validity and reliability - Valera Calero, Juan Antonio; Fernández de las Peñas, César; Fernández Rodríguez, Tomás; Arias Buría, José Luis; Varol, Umut; Gallego Sendarrubias, Gracia María (MDPI, 2021)
Semi-quantitative elastography is a promising imaging technique to evaluate tissue stiffness differences,providing data regarding relative stiffness differences between two targets. The aims of this study were to assess the validity,inter?examiner reliability and variability of semi-quantitative elastography for calculating strain ratios (SR) in a homogeneous gel phantom in different locations within the image. A diagnostic accuracy study was performed in a homogeneous stiffness phantom. Four examiners participated (two novice and two experienced). Each examiner assessed the SR in two locations. Difference between examiners,variability of measurements,SR error and absolute error,mean error of the measurements and coefficient of variation were calculated. The agreement between examiners,validity and variability of measurements were higher in the central area than the lateral areas of the images. Thus,the experience of the examiner was relevant for the concordance of the measurements in the lateral areas of the images (SR difference of 0.14 ± 0.05; p < 0.001),but not for the central area (SR difference of 0.05 ± 0.02; p > 0.05). Our data suggested that semi?quantitative elastography is an accurate tool for assessing small magnitude stiffness differences within the same image in central areas,but the experience of the examiner is a determinant factor. © 2021 by the authors. Licensee MDPI,Basel,Switzerland.
Keywords: 33 Ciencias Tecnológicas::3314 Tecnología médica; ODS 3 - Salud y bienestar